Stealth doxorubicin conjugated bimetallic selenium/silver nanoparticles for targeted cervical cancer therapy. (22nd December 2021) - Malinga, Thoko; Kudanga, Tukayi; Mbatha, Londiwe Simphiwe
Abstract: Bimetallic nanosized delivery systems are attracting a lot of research interest as alternatives to monometallic delivery systems. This study evaluated the ability of bimetallic selenium silver chitosan pegylated folic acid targeted nanoparticles (SeAgChPEGFA NPs) to deliver doxorubicin (DOX) in cervical cancer cells. Comparison studies using monometallic selenium chitosan pegylated folic acid (SeChPEGFA NPs) targeted NPs and free DOX were also conducted. The prepared NPs and their drug nanocomplexes were characterised morphologically and physico-chemically. Drug binding and releasing studies were conducted under a simulated environment in vitro . The cytotoxicity and apoptosis studies were studied using the 3-[(4, 5-dimethylthiazol-2-yl)−2, 5-diphenyl tetrazolium bromide] (MTT) assay and the dual dye staining. The findings revealed that the bimetallic SeAgChPEGFA NPs displayed better colloidal stability, superior physico-chemical qualities, and higher binding abilities in comparison with monometallic SeChPEGFA NPs. In addition, the SeAgChPEGFA NPs showed the pH-triggered controlled drug release and cell-specific cytotoxicity. These findings suggest that the bimetallic NPs are superior delivery systems when compared to their monometallic NPs and free drug counterparts, thus, setting a platform for further in vivo examination.